Análise comparativa e estratificação dos fatores de risco na decisão entre sedação profunda e anestesia geral em pacientes submetidos à colangiopancreatografia retrógrada endoscópica (CPRE) terapêutica - Costa, Eugênio Araújo (2021)
Endoscopic retrograde cholangiopancreatography (ERCP) is an essential surgical procedure in the diagnosis and treatment of a variety of pancreaticobiliary disorders ranging from cholelithiasis to cases of neoplasia. In complex, prolonged and painful endoscopic interventions, such as ERCP, the anesthetic process is performed in order to ensure comfort, cooperation, immobility and effectiveness of the procedure. General anesthesia for ERCP is a well-tolerated and established technique with a low risk of cardiopulmonary complications. However, the growing popularity of deep sedation with propofol as an alternative to general anesthesia for ERCP procedures has stimulated clinical interest in the best anesthetic technique. This study aimed to evaluate and differentiate the profile of clinical, anesthetic and surgical satisfaction response to deep sedation or general anesthesia in patients undergoing therapeutic ERCP. Thus, it consisted of a prospective, interventional clinical trial study, based on the evaluation of a total of 99 patients undergoing therapeutic ERCP procedure under deep sedation (n=50) or general anesthesia (n=49). All patients were followed by the Endoscopy Service of the Hospital Universitário Walter Cantídio at the Universidade de Federal do Ceará (HUWC/UFC), and underwent the surgical procedure of ERCP from January 2020 to December 2020. The present research was submitted and approved by the Research Ethics Committee of the HUWC/UFC (#3.806.254). Patients with risk factors for adverse events underwent general anesthesia, while patients without risk factors underwent deep sedation for ERCP. Associations between the different groups were evaluated regarding anthropometric, epidemiological and clinical variables, related to the time of the ERCP procedure and endoscopic efficiency. As a result, we found that: 1. patients undergoing general anesthesia for ERCP were considered at high risk for cardiovascular complications when compared to patients under deep sedation for ERCP; 2 On the other hand, sedated patients in ERCP evolved with a higher incidence of neurological and respiratory events; 3. exclusively for patients undergoing deep sedation, we found that patients with a BMI>25 had a higher risk of having adverse respiratory and neurological events; STOP-BANG I and II patients had a greater number of respiratory adverse events when compared to STOP-BANG 0 patients; 4. Only 4% of patients required an anesthetic conversion from sedation to general anesthesia, demonstrating that the criteria for defining the choice of anesthetic technique (SMITH et al., 2019) were satisfactory; 5. it was found that all times related to the ERCP procedure were longer in patients undergoing general anesthesia when compared to patients under sedation and, finally, 6. there was greater endoscopic efficiency with the deep sedation technique. Therefore, we conclude that young patients, without coomorbidities, undergoing low-complexity therapeutic ERCP are adequately anesthetized using the deep sedation technique, without significant neurological and/or cardiorespiratory complications. Based on the clinical assessment of the patient's comorbidities, the degree of difficulty of ERCP, in a joint discussion between anesthetist and endoscopist, it is suggested to define the best anesthetic technique for the individuality of each patient.